Organizational Citizenship Behaviour in Public Sector: Does Job Satisfaction Play a Role - Basirudin, Norasherin Binti; Basiruddin, Rohaida; Mokhber, Mozhdeh; Abdul Rasid, Siti Zaleha; Zamil, Nor Aiza Mohd (International Journal of Economics and Financial Issues, 2016)
Employees are regarded as an important asset for organizations, however evaluating their job satisfaction is sometimes dubious. Job satisfaction has been considered as an important factor effecting employee's commitment, behaviour and attitudes in an organization. Previous research found that different inspiration and motivation do exist between public and private sector employees and this will influence job satisfaction over the sectors. Hence, this research aims to determine the perception of job satisfaction among public sector employees. Moreover it will identify which facets of job satisfaction are the most important drivers of organizational citizenship behaviour. Evidently, if public officials are satisfied with their jobs they are more likely to present citizenship behaviour for the goodness of employees, organization as well as the nation without expecting any returns. This is a natural reciprocate of gestures and feedback presenting the satisfaction or dissatisfaction of individuals with their job. Therefore the purpose of this research is to examine the relationship between job satisfaction and organizational citizenship behaviour among public sector employees. This study will be conducted in Malaysian Ministry of Women, Family and Community Development and a quantitative research method will be proposed for data collection. This research will help managers and government bodies to understand the factors affecting job satisfaction among public sector employees and thus enhance their performance. Keywords: Job Satisfaction, Organizational Citizenship Behaviour, Public Sector JEL Classifications: M, M1, M10, M12